2007
DOI: 10.1016/j.cor.2005.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Creating a consensus ranking of proposals from reviewers’ partial ordinal rankings

Abstract: Peer review of research proposals and articles is an essential element in R&D processes world-wide. In most cases, each reviewer evaluates a small subset of the candidate proposals.The review board is then faced with the challenge of creating an overall "consensus" ranking on the basis of many partial rankings. In this paper we propose a branch and bound model to support the construction of an aggregate ranking from the partial rankings provided by the reviewers. In a recent paper we proposed ways to allocate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 13 publications
(14 reference statements)
0
34
0
2
Order By: Relevance
“…A consensus ranking can be seen as an overall ranking that has the highest agreement with a given set of rankings (Cook et al 2007). Different methods to derive the consensus ranking can be found in the literature (Sculley 2007;Svendová and Schimek 2017).…”
Section: Label Rankingmentioning
confidence: 99%
“…A consensus ranking can be seen as an overall ranking that has the highest agreement with a given set of rankings (Cook et al 2007). Different methods to derive the consensus ranking can be found in the literature (Sculley 2007;Svendová and Schimek 2017).…”
Section: Label Rankingmentioning
confidence: 99%
“…Our interest in these problems is motivated by the fa ct that experts are generally selected to meet the evaluation needs of a set of documents rather than randomly assembled together. Thus, unlike in the assignment problems considered in [5,7], minimizing the number of experts is the main objective in the assignments of documents to experts in our work. We consider the assignments of documents to experts without specialties.…”
Section: Introductionmentioning
confidence: 99%
“…The ranking and selection of documents typically relies on cardinal (quantitative) or ordinal (preference) -based comparisons as described in the context of research documents in [6,13]. Cook et al demonstrated that cardinal comparisons such as using average scores of documents could be unreliable especially when experts' scores are not normalized [5][6][7]. They suggested that quantifying the intrinsic values of documents may be difficult, and therefore it is more practical to rely on ordinal rankings.…”
Section: Introductionmentioning
confidence: 99%
“…Ordinal or relative evaluations of documents have been suggested as a more reliable alternative in identifYing high quality documents over cardinal evaluations such as using average scores assigned to the documents by a set of experts [1][2][3][4][5]. Ordinal and cardinal strengths of preferences have also been advocated in [6,8] as natural extensions of ordinal comparison models.…”
Section: Introductionmentioning
confidence: 99%
“…Let A, t, and r be positive integers, where 2 S t < u. A block design (G,B) is called a (u,v,r,t,A)-balanced and incomplete block design (BIBD) if (1) (2) each element in G appears in exactly r blocks, (3) all blocks in B have t elements, and (4) each pair of elements in G appears in exactly A blocks. We have ur = vt since each of the u elements in G appears r times in all the blocks and the union of the blocks as a multiset contains exactly vt elements.…”
Section: Introductionmentioning
confidence: 99%